Long-term trends in concentrations and sources of PM2.5–bound metals and elements in central Los Angeles. (15th May 2021) - Farahani, Vahid Jalali; Soleimanian, Ehsan; Pirhadi, Milad; Sioutas, Constantinos
Abstract: In this study, we investigated long-term trends in the ambient concentrations and sources of redox-active metals and trace elements in central Los Angeles over the period of 2005–2018. Mass concentrations of PM2.5 -bound metals and crustal elements were obtained from the Chemical Speciation Network (CSN) database provided by the US Environmental Protection Agency (US EPA). The recorded metal concentrations showed considerable variations throughout the study period, but they generally followed a descending trend from 2005 to 2018. The decline in annual average concentration of metals was more pronounced for V and Ni. In order to further investigate and interpret the observed decreasing trends, this dataset of 2005–2018 was employed in the positive matrix factorization (PMF) model to determine the contribution of different sources to the total metals' concentrations and their trends over time. Four major sources were identified by the PMF model, including mineral dust, re-suspended road dust, combustion, and tire wear. Mineral dust (50 ± 8%) and re-suspended road dust (38 ± 13%) were the dominant contributors to total metal concentrations, followed by combustion emissions (9 ± 8%) and tire wear (2 ± 1%). While the PMF results showed generally consistent contributions of mineral dust to total metals concentration throughout the investigation period, the contribution of re-suspended road dust to total metals increased from 2013 to 2018 probably due to the increased road traffic (expressed in the form of vehicle miles traveled, VMT) as well as the growing use of electric vehicles (EVs) (which increases resuspension of road dust particles due to their heavy weight) in the area during the same period. In contrast, the contribution of combustion emissions decreased by almost 88% from 2005 to 2018. Using the PMF-resolved factor profiles, we investigated the contribution of the four identified sources to selected individual metals (i.e., Ba, Br, Fe, Ni, Pb, Ti, V, and Zn). The observed decrease in the mass concentration of V and Ni over time was attributed to the reduction in combustion sources and particularly industrial emissions, further corroborating the effectiveness of aftertreatment and air quality policies in reducing the levels of redox-active metals across Los Angeles. Highlights: Metals levels generally decreased from 2005 to 2018 in central LA. Mineral dust, road dust, combustion, and tire wear were major sources of metals. Contribution of combustion to metals decreased due to adopted regulations over time. Road dust emissions increased from 2013 to 2018 due to elevated traffic activities.